# Solve for x and Y: 2x + 2y = 10 2x + y = 7

### 2 Answers | Add Yours

You can use the substitution or elimination method to solve this problem. I will show you how to use both.

Elimination method: subtract one equation from the other in order to eliminate one variable:

2x + 2y = 10

- 2x + y = 7

----------------

0x + y = 3

Therefore, y = 3

Solve for x:

2x+3=7

2x=7-3

2x=4

x=2

Substitution method: rearrange one equation to create an expression for one variable, and *substitute* it into the second equation:

2x+y=7 --> y=7-2x

2x+2(7-2x)=10

2x+14-4x=10

-2x=-4

x = 2

y = 7-2(2)

y = 7-4

y=3

Therefore, x = 2 and y = 3 as solved using both methods.

2x + 2y = 10

2x + y = 7

To solve for " x " and " y " first subtract the top and bottom equation . By subtracting , you should get

y = 3 which is your answer for " y "

Now plug 3 into one of the equation as " y "

2x + 3 = 7 subtract 3 on both side .

By subtracting by 3 on both sides , you should get

2x = 4 now divide both sides by 2

By dividing both sides by 2 , you should get

x = 2 which is your answer for " x "

So " x " = 2 and " y " = 3